POEMS Syndrome with Transient Intracranial Hypertension and Nonspecific Gait Disturbance - Rauniyar, Vivek; Li, Chen; Yang, Huan (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 79-83 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8813